PEMANFAATAN SERAT JERAMI SEBAGAI PAPAN MATRIX COMPOSITE (PMC) - Emon Azriadi (Research Center University of Pahlawan Tuanku Tambusai, 2018)
Kampar Regency is one of the districts that has the largest oil palm plantations in Indonesia, with a plantation area of 241.5 thousand hectares and around 33 Palm Oil Mills (POM). In every palm oil mound industry which rises higher every day, waste in the form of shells and pulp fibers or straw fibers on the ground as large as a soccer field and also emits an unpleasant odor. Only a small portion of this waste is used as boiler fuel. One MCC can produce no less than 100 tons of fiber per week. This fiber has a high economic value, this fiber is easy to get, cheap, does not endanger health can be degredated (biodegradibility) so that if given the right handling with utilization as a composite reinforcing fiber can provide more benefits to the Palm Oil Mill (POM) and the environment in the treatment of these wastes